Injury from domestic violence in the forensic examination (FE) - Mejía Rodríguez, Ulises (2015)
Objective: To determine the injuries from domestic violence and their characteristics. Material and Methods: A prospective descriptive study from January to December 2013. Results: In 2013, 1754 FE were performed, of which 423 were for injuries from domestic violence; 30.97% (131/423) corresponded to patients between 36-49 years. The findings were: 93.14% (394/423) were adults. Regarding the causative agent, 39.48% (167/423) were produced by human nail in assaulted men and women, 21.04% (89/423) blunt agent (hitting, kicking, etc) was the causative agent, the married and cohabiting couples have increased frequency of domestic violence, 45.63% (193/423) of women patients were married, and in males 23.40% (99/423) were married; concerning the injured anatomical region, 8.75% (37/423) of men had lesions in the head and neck and in females 8.98% (38/423). Conclusion: domestic violence injuries are common in males as in females, women have injuries by blunt agents due to the force of male offenders in most cases. Men have human nail injuries.